Increases of negative affect following daily hassles are not moderated by neuroticism: An ecological momentary assessment study. (21st June 2020) - Mey, Lara Kristin; Chmitorz, Andrea; Kurth, Karolina; Wenzel, Mario; Kalisch, Raffael; Tüscher, Oliver; Kubiak, Thomas
Abstract: The occurrence of daily hassles is associated with increased subsequent levels of negative affect. Neuroticism has been found to exacerbate this effect. So far, most research used single‐item measures for the assessment of daily hassles or relied on daily diary studies. This study aimed to examine the interrelations of daily hassles, negative affect reactivity, and neuroticism in daily life employing an extensive inventory of daily hassles. Seventy participants (18–30 years; M = 23.9 years, 59% female) completed a 4‐week smartphone‐based ecological momentary assessment study reporting the occurrence and perceived strain of daily hassles as well as negative affect at five semi‐random signals between 9 a.m. and 8 p.m. Multilevel analyses revealed significant associations between elevated levels of negative affect and higher cumulative daily hassle strain ratings per signal in concurrent and time‐lagged analyses. Contrary to our expectations, there was no moderation by neuroticism on these associations. The results suggest that daily hassles can accumulate in their impact on mood in daily life and exert a prolonged effect on negative affect. The absence of a significant moderation by neuroticism may be interpreted in the light of methodological specifics of this study.